2020
DOI: 10.1111/cas.14396
|View full text |Cite|
|
Sign up to set email alerts
|

Role of increased vascular permeability in chemotherapy‐induced alopecia: In vivo imaging of the hair follicular microenvironment in mice

Abstract: Chemotherapy‐induced alopecia is one of the most difficult adverse events of cancer treatment for patients. However, it is still unknown why anticancer drugs cause hair loss. We aimed to clarify the mechanism of chemotherapy‐induced alopecia in mice using an in vivo imaging technique with a two‐photon microscope, which enables observation of the deep reaction in the living body in real time. In this study, ICR mice were injected intraperitoneally with cyclophosphamide (120 µg/g). Changes in the hair bulb morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…CYP has been reported to have a high sensitivity to vascular endothelial cells and to induce apoptosis of vascular endothelial cells 24 . Previously, we have also reported that the pathological condition of increased vascular permeability is potentially due to the induction of apoptosis in those vascular endothelial cells 15 . We demonstrated that the suppression of this pathological condition may promote hair recovery, and that the effectiveness of these treatments may be due to the regulation of this pathological condition.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…CYP has been reported to have a high sensitivity to vascular endothelial cells and to induce apoptosis of vascular endothelial cells 24 . Previously, we have also reported that the pathological condition of increased vascular permeability is potentially due to the induction of apoptosis in those vascular endothelial cells 15 . We demonstrated that the suppression of this pathological condition may promote hair recovery, and that the effectiveness of these treatments may be due to the regulation of this pathological condition.…”
Section: Discussionmentioning
confidence: 53%
“…While an adult mouse model was used in this study, it has been reported that by aligning the growth phase through hair removal, the growth phase shifts from mature anagen to catagen by the 15th day, and enters the mature anagen phase again after the 30th day 16,17 . In a previous study, we also reported that changes occurred in the perifollicular area 24 h after anticancer drug administration 15 . Therefore, in this study, the 10th day, 24 h after administration of CYP was evaluated as early phase, the 16th day as middle phase, and the 37th day as late phase.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations